Influence of heavy metals on protein secretion in saccharomyces cerevisiae - Della Vedova, Maria Cecilia (2021)
The extracellular secretions are believed to have a significant influence on the microorganisms physicochemical properties related to growth and morphological preservation. To study the behavior of yeast against metals through the analysis of changes in the secreted protein profiles, we worked with the collection strain, Saccharomyces cerevisiae ATCC 32051, which was cultured in EG medium (g/L: Glucose 10; K2HPO4 0.5; KH2PO4 0.5; Yeast extract 1) supplemented or not with 30 mgL-1 Cu(II) (as CuSO4.5H2O) or Cr(VI) (as K2Cr2O7). The Cu(II) and Cr(VI) concentrations were determined according to the minimum inhibitory concentration study. The extracellular proteins were obtained from the cell-free supernatants of cultures grown in the presence and absence of Cu(II) and Cr(VI) at 200 rpm and 30 °C during 48 h. The cell-free supernatants wereobtained from the centrifugation of the cultures and filtered with nitrocellulose membranes with a retention pore of 0.2 μm. Then, they were concentrated at 20X using Vivaspin Turbo 15, 3000 MWCO ultrafiltration devices with polyethersulfone (PES) membrane. The samples were analyzed by shotgun proteomic techniques using nanoUHPLC-ESI-MS/MS. Bioinformatic analysis was performed using Swiss-Prot database specific for S. cerevisiae and MASCOT v2.5.1. Thecomparative analysis of the protein expression was carried out using ProteoIQv2.8. A total of 190 proteins were identified, of which 55 proteins were only expressed in the control cells (Co, grown without heavy metals); 9 proteins were found in the presence of Cr(VI) and 23 proteins when the yeast grew in the presence of Cu(II). The remaining 45 proteins were shared by S. cerevisae in the three culture conditions. However, when using the CELLOv2.5 online tool to predict the location of the identified proteins, only five proteins in the control group, 15 under the Cu (II) exposure, and three in the Cr(VI) exposed biomass showed a significant probability to be secreted into the extracellular space. A semi-quantitative and comparative analyses of the relative abundance profiles were performed on the 45 extracellular proteins found in the three conditions. Theanalysis of the extracellular proteins obtained in the presence of Cu (II) showed that only two proteins were over-expressed, which are involved in the binding of bivalent metal ions and in carbohydrate biosynthesis. Likewise, 19 proteins were downregulated. In the presence of Cr (VI), 20 proteins were down-regulated and 3 were over-expressed, which are constituents of the ribosome and are involved in the Zn ion binding. The results obtained indicate that S. cerevisiae responds by adjusting the protein expression to carry out its normal cellular functions. In addition, the differential expression of proteins present in the extracellular space was observed, which could be crucial in the sequestration and transport of the metals, fundamental to reduce the toxic effects that Cu (II) and Cr(VI) could exert on the cells.